2003
DOI: 10.1177/08830738030180011001
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy, Intelligence, and Psychiatric Disorders in Patients With Cerebellar Hypoplasia

Abstract: The cerebellum is involved in motor and cognitive functions and behavior. Its role in controlling epileptic seizures has been demonstrated in the literature. Genetic factors can enhance epilepsy susceptibility when the cerebellum is damaged. We examined the occurrence and features of epilepsy, intelligence, and psychiatric disorders in 28 patients with cerebellar hypoplasia. We compared patients with (10; 35.7%) and without (18; 64.3%) epilepsy. The statistical evaluation showed a significant prevalence of fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(29 reference statements)
1
9
0
2
Order By: Relevance
“…Parmeggiani et al 36 studied 28 patients with cerebellar hypoplasia and, after finding out that 75% of them had MR, they concluded that cerebellar hypoplasia is an important risk factor for MR. Nordin & Gillberg 37 studied 177 individuals with MR or motor deficiency and observed that the prevalence of autistic spectrum disorders in 101 children with MR was of 19.8%. The authors highlighted that many children with severe MR have autistic spectrum disorders, but not the majority of them.…”
Section: Epidemiology Of Mental Retardationmentioning
confidence: 99%
“…Parmeggiani et al 36 studied 28 patients with cerebellar hypoplasia and, after finding out that 75% of them had MR, they concluded that cerebellar hypoplasia is an important risk factor for MR. Nordin & Gillberg 37 studied 177 individuals with MR or motor deficiency and observed that the prevalence of autistic spectrum disorders in 101 children with MR was of 19.8%. The authors highlighted that many children with severe MR have autistic spectrum disorders, but not the majority of them.…”
Section: Epidemiology Of Mental Retardationmentioning
confidence: 99%
“…Sonuç olarak serebellum disfonksiyonu ile epileptik nöbetler arasındaki patofizyolojik mekanizmalar net olarak anlaşılamamış olsa da başlıca hayvan modellerinde yapılan çalışmalar, serebellumun epileptik nöbet aktivitesi üzerinde inhibitör etkisi olduğunu göstermektedir (20,21). Ayrıca hem hayvan hem insanda yapılan çalışmalar, serebellumun stimülasyonunun nöbet aktivitesini düzelttiğini veya nöbet süresini kısalttığını göstermektedir.…”
Section: Discussionunclassified
“…Cerebellar congenital abnormalities represent a risk factor for epileptic seizure occurrence and/or cognitive and behavior disorders [13][14][15][16][17] ; mental retardation and autism are more frequent in cases with cerebellar hypoplasia. 18 In our patients with familial antecedents for epilepsy, seizures-focal in the first two, apparently generalized in the third-were not frequent and eventually disappeared.…”
Section: Discussionmentioning
confidence: 99%